Shadow city : a Horngate witches book - Francis, Diana Pharaoh (New York, N.Y. : Pocket Books, 2012)
Forced to become the champion of a demigod in a deadly game where the losers meet a fate worse than death, warrior Max, alone and unarmed in a strange, magical city, will stop at nothing to defeat her enemies and return home to Horngate.
Keywords: Witches -- Fiction; Magic -- Fiction; Good and evil -- Fiction